2003
DOI: 10.1097/00042737-200310000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Isolated oesophageal involvement of Crohn's disease

Abstract: A 31-year-old male was admitted with complaints of dysphagia and odynophagia. An upper gastrointestinal tract series revealed inflammatory changes in the mid and distal oesophagus with intramural extravasation of the barium. An upper endoscopy showed multiple ulcerations and inflammation. The patient developed a large stricture with no response to serial endoscopic dilations and a surgical resection of the oesophagus was required. Gross examination of the surgical specimen revealed transmural inflammation, dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 16 publications
0
32
0
Order By: Relevance
“…Dysphagia and odynophagia are the most common symptoms 2 6. Other symptoms include heartburn and chest pain 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dysphagia and odynophagia are the most common symptoms 2 6. Other symptoms include heartburn and chest pain 2.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 30% of patients have oral aphthous ulcerations2 10 at the time of oesophageal CD symptom onset. Weight loss associated with these symptoms can be found 3 6 11. Extra intestinal manifestations of CD are often present, including arthritis, uveitis, and erythema nodosum 12…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1a-c). In severe cases, longitudinally aligned ulcers, a cobblestone appearance and fistulas are observed [20][21][22][23]. Decker et al reported that the incidences of esophageal lesions, including ulcer, erosion, stricture and fistula, were 85, 40, 20 and 5%, respectively [20].…”
Section: Esophageal Lesionsmentioning
confidence: 99%
“…However, these lesions are not specific to CD and must therefore be distinguished from other diseases, such as gastro-esophageal reflux disease, eosinophilic esophagitis, drug-induced esophagitis, viral and fungal infection, tuberculosis, vasculitis and malignancies [24]. Granuloma is detected in \25% of esophageal biopsy specimens (Table 2) [22,25,26]; thus, even in cases in which granulomas is not detected, it is important to treat the case as CD, because the diagnosis of CD can be made endoscopically.…”
Section: Esophageal Lesionsmentioning
confidence: 99%